Serotypes and pyocinetypes of Pseudomonas aeruginosa - Vaz, Tânia Mara Ibelli (1989)
195 Pseudomonas aerug inosa strains, most of them isolated from blood and cerebro spinal fluid cultures, were serotyped by slide agglutination test. The serotypes 0:6 and 0:11 were the prevalent types with 25,64% and 20,54% respectively. The serotypc 0:10 caused a meningitis outbreak involving maily children less than one year of age, in 1974 during meningococcal epidemic in São Paulo City. By Fyfe piocina typing method, 12 piocine types were disclosed among the serotypes with the predominance of pyocine types 1,3 and 10 that accounted for almost 90% of all typed strains. It's stressed the combined use of the serological and pyocine typing method in order to differenciate isolates belonging to the same serotype.